Outcome measures associated with perceived stress - Hall, Deborah A. (Springer International Publishing, 2017)
We tend to think of situations in life as stressful when they are unpredictable, uncontrollable or overloading. Stress is a very personal experience. Perceived stress is a reflection of how such external stressful events and everyday hassles are ‘filtered’ according to our individual personality traits and coping strategies. People with tinnitus describe various stress-related complaints, but these symptoms are not just restricted to tinnitus. Poor concentration, sense of loss of control, sleep disturbance and irritability are also shared with people who are experiencing a state of generalised anxiety or depression. Whatever their origin, the goal of any clinical intervention for people with tinnitus should be to reduce these negative symptoms. This chapter takes a look at the way in which perceived stress associated with tinnitus has been measured. My focus is on clinical trials, but I start from the perspective of questionnaire construction by describing and comparing tinnitus-specific and general stress measures. I then evaluate how these instruments have been applied in a range of contemporary tinnitus trials. The chapter includes tutorials that introduce the reader to fundamental concepts in clinical trial design, understanding the purpose of questionnaires and appreciating the relevance of sample size calculations.